Gender Dependent Evaluation of Autism like Behavior in Mice Exposed to Prenatal Zinc Deficiency - Grabrucker, Stefanie; Boeckers, Tobias M.; Grabrucker, Andreas M. (Frontiers in Behavioral Neuroscience, 2016)
Zinc deficiency has recently been linked to the etiology of autism spectrum disorders (ASD) as environmental risk factor. With an estimated 17% of the world population being at risk of zinc deficiency, especially zinc deficiency during pregnancy might be a common occurrence, also in industrialized nations. On molecular level, zinc deficiency has been shown to affect a signaling pathway at glutamatergic synapses that has previously been identified through genetic mutations in ASD patients, the Neurexin-Neuroligin-Shank pathway, via altering zinc binding Shank family members. In particular, prenatal zinc deficient but not acute zinc deficient animals have been reported to display autism like behavior in some behavioral tests. However, a full behavioral analysis of a possible autism like behavior has been lacking so far. Here, we performed an extensive behavioral phenotyping of mice born from mothers with mild zinc deficiency during all trimesters of pregnancy. Prenatal zinc deficient animals were investigated as adults and gender differences were assessed. Our results show that prenatal zinc deficient mice display increased anxiety, deficits in nest building and various social interaction paradigm, as well as mild alterations in ultrasonic vocalizations. A gender specific analysis revealed only few sex specific differences. Taken together, given that similar behavioral abnormalities as reported here are frequently observed in ASD mouse models, we conclude that prenatal zinc deficient animals even without specific genetic susceptibility for ASD, already show some features of ASD like behavior.